Phosphorylation of FOXN3 by NEK6 promotes pulmonary fibrosis through Smad signaling - Yu, Jinjin; Li, Yingke; Li, Yiming; Liu, Xiaotian; Huo, Qingyang; Wu, Nan; Zhang, Yangxia; Zeng, Taoling; Zhang, Yong; Li, Henry You; Lian, Jie; Zhou, Jihong; et al. (Nature communications, 2025)
The transcriptional repressor FOXN3 plays a key role in regulating pulmonary inflammatory responses, which are crucial in the development of pulmonary fibrosis. However, its specific regulatory function in lung fibrosis remains unclear. Here, we show that FOXN3 suppresses pulmonary fibrosis by inhibiting Smad transcriptional activity. FOXN3 targets a substantial number of Smad response gene promoters, facilitating Smad4 ubiquitination, which disrupts the association of the Smad2/3/4 complex with chromatin and abolishes its transcriptional response. In response to pro-fibrotic stimuli, NEK6 phosphorylates FOXN3 at S412 and S416, leading to its degradation. The loss of FOXN3 inhibits β-TrCP-mediated ubiquitination of Smad4, stabilizing the Smad complex’s association with its responsive elements and promoting transcriptional activation, thus contributing to the development of pulmonary fibrosis. Notably, we found a significant inverse expression pattern between FOXN3 and Smad4 in clinical pulmonary fibrosis cases, underscoring the importance of the NEK6-FOXN3-Smad axis in the pathological process of pulmonary fibrosis. This study identifies FOXN3 as a suppressor of pulmonary fibrosis by inhibiting Smad signaling. FOXN3 facilitates Smad4 ubiquitination, disrupting the Smad complex’s association with target elements and abolishing its transcriptional activity.